A criança e o adolescente com problemas do desenvolvimento no ambulatório de pediatria - MIRANDA, Luci Pfeiffer (2015)
OBJECTIVE: to review the literature on outpatient care of children and adolescents with developmental disabilities, focusing on prevention, early diagnosis, treatment, outcomes and rehabilitation. SOURCES OF DATA: search of Medline and Lilacs databases; publications of scientific committees of institutions for children with special needs; and outpatient care reports of reference centers for the treatment of children and adolescents with mental and developmental disabilities. SUMMARY OF THE FINDINGS: this population presents health problems associated with the basic pathology and its consequences in addition to the usual problems of the specific age group. The etiology of developmental disorders and the main characteristics of each type of disability are discussed. Special attention is given to outpatient pediatric care. CONCLUSIONS: the most recent study of the Brazilian population, performed in 2000, showed that 14.5% of this population presented some type of developmental deficiency. Therefore, developmental problems are one of the most prevalent health problems among children and adolescents. Consequently, pediatricians need to be prepared to evaluate and identify factors that may influence normal children development. Pediatricians are responsible for prevention, early diagnosis and coordination of the multidisciplinary treatment of these patients in addition to basic medical assistance, which is essential to guarantee the patients' good quality of life.